2011
DOI: 10.1093/humrep/der228
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting the cumulative outcome of IVF/ICSI treatment: a multivariable analysis of 2450 patients

Abstract: background: Knowing predictors of pregnancy in IVF is helpful for clinicians to individualize the treatment plans and improve patient counseling and for patients to decide whether to undergo infertility treatment. The aim of the study was to identify independent predictors of the chance of clinical pregnancy after a completed IVF/ICSI cycle (fresh plus cryopreserved embryos transferred from one stimulated cycle) and to compare the predictive value of important predictors identified. results:The following nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 36 publications
6
71
1
2
Order By: Relevance
“…Some have focused on factors predicting pregnancy after fresh embryo transfer [1], whereas others have focused on predicting the cumulative outcome of a completed IVF cycle, which includes a fresh cycle and/or subsequent frozen cycles [2]. Very few previous works have examined whether predictors of cumulative outcome still retain their predictive value in a fresh cycle or vice versa.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some have focused on factors predicting pregnancy after fresh embryo transfer [1], whereas others have focused on predicting the cumulative outcome of a completed IVF cycle, which includes a fresh cycle and/or subsequent frozen cycles [2]. Very few previous works have examined whether predictors of cumulative outcome still retain their predictive value in a fresh cycle or vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al found that the size and quality of the embryo cohort are the strongest predictors of cumulative outcome in a completed treatment cycle [2]. Jun et al concluded that embryo cohort-specific variables are more informative than any measures of individual transferred embryos in a fresh cycle [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from studies on the role of endometrial thickness on implantation and live births are contradictory. While some authors reported that there is not a relationship [16,17], there is one retrospective study that shows that there is a steady and gradual increase in pregnancy rates as endometrial thickness increases [18]. Furthermore, the last authors claimed that this relationship exists independent of maternal age and embryo quality.…”
Section: Prp and Human Reproductionmentioning
confidence: 99%
“…The most important factors are maternal age and Antimüllerian hormone (AMH) level [1,2]. The number and quality of the embryos available for transfer also play an essential role [1,3,4]. Different models predicting IVF success rate have been proposed, taking into account clinical and embryological data [5][6][7].…”
Section: Introductionmentioning
confidence: 99%